Etika dan Bisnis Sebagai Strategi Bisnis Jangka Panjang Pada Era Global - Ainun Pratiwi Harahap; M. Yarham (STIKes Ibnu Sina Ajibarang, 2023)
When it comes to developing connections with other parties in the corporate sector, ethics is crucial. Business ethics is critical in deciding a company's success or failure. Implementing excellent business ethics may help increase communication and promote mutual trust among coworkers. You must concentrate on two things while operating a business. The first is to be aware of and sensitive to the needs and feelings of others. The second purpose is to prevent misunderstandings with others, since business ethics differ widely between cultures and nations. The goal of this essay is to discover how Ethics and Business might become long-term business strategies in the Global Business Era. As a research approach, the author of this paper use observation techniques as well as library research methods. According to the findings of this article's discussion, business ethics influences the amount of confidence that each member of the business community has in one another. The company, suppliers, and end users are all stakeholders who impact one another. Each of these components must adhere to high ethical standards in order to preserve the foundation of trust.